2019
DOI: 10.1093/her/cyz013
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer knowledge and screening adherence among low-income Hispanic employees

Abstract: Hispanics have the lowest colorectal cancer (CRC) screening rates of all racial/ethnic groups and comprise the largest proportion of low-income manual laborers in the nation. We partnered with businesses to implement a community health worker (CHW)-led intervention among Hispanic workers in service-related and manual labor occupations, which often pay low wages and do not provide health insurance. CHWs measured knowledge, screening adherence and perceptions of CRC risk before and after educational intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Cancer risk perception by hereditary risk may not be a decisive factor that drives genetic testing and other preventive care uptakes. Prior studies on cancer risk perception and screening adherence also found no significant association among racial and ethnic minorities [ 33 , 34 ]. It is also possible that racial and ethnic minority groups may face greater difficulty accessing cancer genetic testing despite higher cancer risk perception (e.g., testing cost burden, distrust in health provider) [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer risk perception by hereditary risk may not be a decisive factor that drives genetic testing and other preventive care uptakes. Prior studies on cancer risk perception and screening adherence also found no significant association among racial and ethnic minorities [ 33 , 34 ]. It is also possible that racial and ethnic minority groups may face greater difficulty accessing cancer genetic testing despite higher cancer risk perception (e.g., testing cost burden, distrust in health provider) [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although LS carriers carry significant lifetime risk for the development of CRC regardless of ethnicity and race, patients belonging to racial and ethnic minorities in the United States are less likely to receive genetic evaluation for inherited CRC syndromes and may not receive sufficient screening following diagnosis ( 15 ). This discrepancy has been correlated to a lack of patient education on adequate screening modalities leading to stigmatization of screening practice, the potential effects of oncologists’ implicit biases in patient-physician interactions, and the insurance disparities between Hispanic and non-Hispanic populations ( 16 18 ). In contrast to the literature, we showed no significant difference in interval screening between Hispanics and non-Hispanics in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…There were some missing responses, and these are noted in the tables. Questions pertaining to colorectal cancer screening were derived from the 2015 US Behavioral Risk Factor Surveillance System (BRFSS) survey [ 15 ] and have previously been applied in community surveys conducted by our team among immigrant and non-English speaking participants in the United States [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%